THE INFLUENCE OF AYURVEDIC HERBAL REMEDIES FOR DIABETES MELLITUS- A HOLISTIC APPROACH - Dr. Anantkumar V. Shekokar; Dr. Kanchan A. Shekokar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Diabetes is a heterogenous disease of carbohydrate metabolism characterized by hyperglycaemia with polyuria, polypepsia, and polydipsia, due to lack of secretion of insulin or resistance to insulin. Several distinct types of DM exist and are caused by a complex interaction of genetics, environmental factors and lifestyle choices. DM will likely continue to be the leading cause of morbidity and mortality in near future. It is projected that the number of individuals with DM will continue to rise in the near future. The usual methods for diagnosing diabetes are based on various chemical tests of urine and the blood viz, Fasting Blood Glucose Level, Glucose Tolerance Test, Urinary Sugar, and Glycated Hemoglobin (HBA1c). Glucose intolerance and type 2 diabetes may also be manifestations of an underlying disorder known as the metabolic syndrome. Besides modem medicines, there are many herbal formulations placed in the market with different claims and benefits. Most of the herbal formulations are made available as solid dosage forms like capsules, tablets and powders. They are not presented as liquid orals due to risk of their sugar content. Asavas and Arishtas invention allows the manufacturer to prepare herbal composition for diabetes in the form of a liquid oral with prolonged shelf life and without disadvantage of sugar content.